Maternal phyogeopgraphy of brown bears (Ursus Arctos) and testing the utility of non-invasive genetic samples - Çilingir, Fatma Gözde (Middle East Technical University, 2012)
The genetic diversity and phylogeography of brown bear maternal lineages have been studied extensively over the last two decades. In this study the genetic diversity and maternal phylogeography of non-invasively sampled 35 brown bears, including 5 captive individuals were reported from Turkey. In addition to the optimization of DNA extraction from hair, faeces and old skin samples and their PCRs, Bayesian phylogenetic analyses based on a 269 bp long piece of bear mitochondrial DNA were conducted and 14 novel haplotypes belonging to three major lineages were revealed. The most widespread lineage was found to be the “Eastern” clade 3a, while geographically more restricted “Western” and “Middle Eastern” lineages were reported for the country for the first time. A specimen from the Taurus range (southern Turkey) was shown to be closely related to the presumably extinct bears in Lebanon. Moreover, a unique novel lineage that appears to have split early within the Middle Eastern clade was defined. Despite limited sampling, this study demonstrates a high level of mitochondrial diversity in Turkish brown bears, extends the ranges of both European and Middle Eastern clades into Turkey, and identifies a new divergent lineage of possibly wider historical occurrence while demonstrating the significance of non-invasive genetic sampling for such analysis. M.S. - Master of Science